Household debt and saving during the 2007 recession - Rajashri Chakrabarti; Donghoon Lee; Wilbert van der Klaauw; Basit Zafar (Federal Reserve Bank of New York, 2011)
Using credit report records and data collected from several household surveys, we analyze changes in household debt and saving during the 2007 recession. We find that, while different segments of the population were affected in distinct ways, depending on whether they owned a home, whether they owned stocks, and whether they had secure jobs, the crisis' impact appears to have been widespread, affecting large shares of households across all age, income, and education groups. In response to their deteriorated financial situations, households reduced their average spending and increased their saving. This increase in saving - at least in 2009 - did not materialize through an increase in contributions to retirement and savings accounts. If anything, such contributions actually declined on average during that year. Instead, the higher saving rate appears to reflect a considerable decline in household debt, as households paid down mortgage debt in particular. At the end of 2009, individuals expected to continue increasing their saving and paying down of debt, which is consistent with what we have observed so far in 2010. In contrast, consumers were pessimistic about the availability of credit, expecting it to become harder to obtain during 2010.
Keywords: G01; D14; D12; D91; 330; household debt and saving; 2007 recession; credit access; mortgage debt; Finanzmarktkrise; Privater Haushalt; Haushaltsökonomik; Schulden; Sparen; Verschuldungsrestriktion; Kredittilgung; USA